Identification of Alternative Physician Assistant Recertification Models: An Analysis of the Landscape and Evidence Surrounding Approaches to Recertification in the Health Professions - Reid, Rachel O. (Rand Health Q, 2020)
Health professional recertification is intended to be a mechanism for demonstration and fostering of professional knowledge and competence. Recertification requirements vary among health professions and are evolving over time. RAND Corporation researchers assessed the landscape of recertification requirements for physician assistants (PAs), advanced practice nurses (APNs), and physicians in the United States and other countries through an environmental scan, reviewed the literature regarding the impact of recertification requirements on patients and health professionals, and conducted semi-structured interviews with certifying organization representatives. Recertification requirements vary, including continuing education, exams or assessments, and other activities. Closed-book exams are most common in the United States. PA recertification currently requires a high-stakes closed-book exam; a pilot of a longitudinal assessment with smaller, regularly spaced batches of questions is planned. Many allopathic physician specialty boards are transitioning from recertification exams to longitudinal assessments; most osteopathic specialty boards require recertification exams. An exam is required for certified registered nurse anesthetist recertification, but not for other APNs. Evidence regarding the effects of recertification requirements on health professionals and patients for PAs, APNs, and professionals outside the United States is limited. The evidence mainly focuses on U.S. allopathic physicians. Physicians have mixed opinions about trade-offs between burden and professional benefit, and some, but not all, studies find associations between recertification and indicators of better care. Major themes reflected in interviews with certifying organizations included a desire to balance evaluative and educational goals, the tension felt between public responsibility and health professional preferences, and burden and applicability to practice.